2016
DOI: 10.1016/j.bbmt.2016.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Medical Students' Knowledge, Familiarity, and Attitudes towards Hematopoietic Stem Cell Donation

Abstract: Hematopoietic stem cell transplantation (HSCT) is a potentially curative treatment for patients with blood disorders and genetic diseases. Approximately 70% of the HSCTs currently performed in the United States use stems cells from an unrelated donor who donated voluntarily. Medical students (MS) are a young, diverse, influential population whose willingness to engage in altruistic acts, such as donating stem cells, may be correlated with knowledge on the topic. A literature gap exists in MS perspectives towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 24 publications
4
42
0
Order By: Relevance
“…Blood donors are more likely to register as potential HPC donors than people without history of blood donation [11,12]. In our study, blood donors constituted 36.6% of PBSC donors.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Blood donors are more likely to register as potential HPC donors than people without history of blood donation [11,12]. In our study, blood donors constituted 36.6% of PBSC donors.…”
Section: Discussionmentioning
confidence: 81%
“…There are many donor-dependent factors influencing the outcome of the procedure, such as gender, age, ethnicity, body mass index (BMI), smoking, iron status, pre-G-CSF platelet count, Correspondence: Krzysztof Bartnik, Department of Hematology, Oncology and Internal Medicine, Medical University of Warsaw, Banacha 1a, Warsaw 02-097, Poland E-mail: krzysztof46bartnik@gmail.com pre-G-CSF mononuclear count, pre-G-CSF white blood cell (WBC) count or weight difference between the donor and the recipient [3][4][5][6][7][8][9][10]. Studies show that people with a history of blood donation are more likely to register as potential haematopoietic progenitor cell (HPC) donors, yet to our best knowledge, there is a lack of data in the literature regarding the impact of prior blood donation on the outcome of HPC mobilization outcomes [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…This is also evident in a previous study [7], which cited difficulties experienced by donors, including receiving inadequate information and delays in the process due to the lack of understanding of medical staff. Because healthcare providers are a source of health information and advice, it is necessary to assess their knowledge, attitudes, and behavior regarding HSCD [24]. Therefore, healthcare providers should have appropriate knowledge of and supportive attitudes towards HSCD.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, healthcare providers should have appropriate knowledge of and supportive attitudes towards HSCD. The need to include HSCD education in school curricula has been argued for [24]; this could generate more interest in HSC donor registration [25]. In other words, through active education, healthcare providers should be the main agents with sufficient knowledge and positive views of HSCD to help provide respect and support for donors [7].…”
Section: Discussionmentioning
confidence: 99%
“…Providing accurate information and knowledge about stem cell donation remains a priority in increasing the number of donations. Recent studies have demonstrated that also educational and communicative efforts towards the medical community may be beneficial in the recruitment and retention of donor populations [61, 62]. The creation of a social and cultural atmosphere favouring the diffusion of correct and proper information regarding HSC donation is central in encouraging people to make a donation.…”
Section: Bioethical Issuesmentioning
confidence: 99%